2022
DOI: 10.1590/s1677-5538.ibju.2022.0119
|View full text |Cite
|
Sign up to set email alerts
|

The role of hyperbaric oxygen therapy in Fournier’s Gangrene: A systematic review and meta-analysis of observational studies

Abstract: Purpose: Purpose: Management of Fournier's Gangrene (FG) includes broad-spectrum antibiotics Management of Fournier's Gangrene (FG) includes broad-spectrum antibiotics with adequate surgical debridement, which should be performed within the first 24 hours with adequate surgical debridement, which should be performed within the first 24 hours of onset. However, this treatment may cause significant loss of tissue and may delay of onset. However, this treatment may cause significant loss of tissue and may delay h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Raizandha et al 49 demonstrated a significant reduction in mortality in patients of FG receiving HBOT but noted no reduction in the number of debridements and the mean length of hospital stay.…”
Section: Adjuvant Treatmentsmentioning
confidence: 99%
“…Raizandha et al 49 demonstrated a significant reduction in mortality in patients of FG receiving HBOT but noted no reduction in the number of debridements and the mean length of hospital stay.…”
Section: Adjuvant Treatmentsmentioning
confidence: 99%
“…To date, the clinical management of FG consists of extensive surgical debridement, fascia incision, the drainage of necrotic tissue, and sufficient intravenous administration of broad-spectrum antibiotics [ 3 ]. Moreover, recent studies have also highlighted the potential benefits of hyperbaric oxygen therapy [ 4 ]; however, its application is still limited, due to challenges in accessing and transferring patients to units that offer this service.…”
Section: Introductionmentioning
confidence: 99%